2011
DOI: 10.1007/s10584-011-0331-2
|View full text |Cite
|
Sign up to set email alerts
|

A trend analysis of normalized insured damage from natural disasters

Abstract: This document is the author's final manuscript accepted version of the journal article, incorporating any revisions agreed during the peer review process. Some differences between this version and the published version may remain. You are advised to consult the publisher's version if you wish to cite from it.Electronic copy available at: http://ssrn.com/abstract=1831633

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(83 citation statements)
references
References 33 publications
4
78
0
1
Order By: Relevance
“…The reduction of flood losses could potentially be tackled quite dramatically in the short to medium term via reduction of exposure and vulnerability of populations to flood risk. Analysis of economic and insured losses have been carried out extensively by Pielke (2000;, Munich Re (2001;2004a;2004b;, Barthel and Neumayer (2010), Crompton andMcAneney 2008, Swiss Re (2010) and others. These studies demonstrate that the attribution of increased losses across exposure, vulnerability and hazard is currently weighted towards exposure and vulnerability rather than hazard.…”
Section: Numbers Affectedmentioning
confidence: 99%
“…The reduction of flood losses could potentially be tackled quite dramatically in the short to medium term via reduction of exposure and vulnerability of populations to flood risk. Analysis of economic and insured losses have been carried out extensively by Pielke (2000;, Munich Re (2001;2004a;2004b;, Barthel and Neumayer (2010), Crompton andMcAneney 2008, Swiss Re (2010) and others. These studies demonstrate that the attribution of increased losses across exposure, vulnerability and hazard is currently weighted towards exposure and vulnerability rather than hazard.…”
Section: Numbers Affectedmentioning
confidence: 99%
“…Economic losses due to weather-and climate-related disasters have increased over the past decades (Barthel and Neumayer, 2012;IPCC, 2012). Between 1980 and 2007 a total of about 1.42 million people were killed and over USD 900 billion in financial loss were observed globally (WMO, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies from Mexico and Colombia highlight both variability and positive trends in disaster frequency (unadjusted) losses and other damage metrics (Saldaña-Zorrilla and Sandberg, 2009;Marulanda et al, 2010;Rodriguez-Oreggia et al, 2013). However, the greatest contributor to increased cost is rising exposure associated with population growth and growing value of assets (high confidence; Bouwer et al, 2007;Bouwer, 2011;Barthel and Neumayer, 2012;Handmer et al, 2012, their Sections 4.2.2, 4.5.3.3, Box 4-2). To account for changes over time in the value of exposed assets, many studies attempt to normalize monetary losses by an overall measure of changes in asset value.…”
Section: Economic Losses Due To Extreme Weather Eventsmentioning
confidence: 99%
“…A majority of studies have found no detectable trend in normalized losses (Bouwer, 2011). Studies on insured losses that in general meet higher data quality standards than data on overall losses due to thoroughly monitored payouts have focused on developed countries including Australia, Germany, Spain, the USA (Changnon, 2007(Changnon, , 2008(Changnon, , 2009aBarredo et al, 2012;Barthel and Neumayer, 2012;Sander et al, 2013; see also Section 10.7.3). Studies of normalized losses from extreme winds associated with hurricanes in the USA (Miller et al, 2008;Pielke Jr. et al, 2008;Schmidt et al, 2010;Bouwer and Botzen, 2011) and the Caribbean (Pielke Jr. et al, 2003), tornadoes in the USA (Brooks and Doswell, 2002;Boruff et al, 2003;Simmons et al, 2013), and wind storms in Europe (Barredo, 2010) have failed to detect trends consistent with anthropogenic climate change, although some studies were able to find signals in loss records related to climate variability, such as damage and loss of life due to wildfires in Australia related to ENSO and Indian Ocean dipole phenomena (Crompton et al, 2010), or typhoon loss variability in the western North Pacific (Welker and Faust, 2013).…”
Section: Economic Losses Due To Extreme Weather Eventsmentioning
confidence: 99%